Structural analysis and molecular substrate recognition properties of Arabidopsis thaliana ornithine transcarbamylase, the molecular target of phaseolotoxin produced by Pseudomonas syringae - Nielipinski, Maciej; Pietrzyk-Brzezinska, Agnieszka J.; Wlodawer, Alexander; Sekula, Bartosz (Frontiers in Plant Science, 2023)
Halo blight is a plant disease that leads to a significant decrease in the yield of common bean crops and kiwi fruits. The infection is caused by Pseudomonas syringae pathovars that produce phaseolotoxin, an antimetabolite which targets the arginine metabolism, particularly by inhibition of ornithine transcarbamylase (OTC). OTC is responsible for production of citrulline from ornithine and carbamoyl phosphate. Here we present the first crystal structures of the plant OTC from Arabidopsis thaliana (AtOTC). Structural analysis of AtOTC complexed with ornithine and carbamoyl phosphate reveals that OTC undergoes a significant structural transition when ornithine enters the active site, from the opened to the closed state. In this study we discuss the mode of OTC inhibition by phaseolotoxin, which seems to be able to act only on the fully opened active site. Once the toxin is proteolytically cleaved, it mimics the reaction transition state analogue to fit inside the fully closed active site of OTC. Additionally, we indicate the differences around the gate loop region which rationally explain the resistance of some bacterial OTCs to phaseolotoxin.